Psychological Well Being ditinjau dari Perilaku Prososial pada Siswa - Angellina; Anissa Mifthahurahma Sihombing; Emelia Debora Pinem; Sri Hartini (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
Adolescent development period is a critical period where there is a transition of development from childhood to adulthood about their mental function, physical, and their psychological. For the sake to support teenager can grow in accordance with their mental age, teenagers are expected to have a high psychological well-being. Give them a chance to get involve in an useful activity so that can increase their willingness to engage in prosocial behavior in the future. Based on the above background this study aims to determine whether there is a relationship between prosocial behavior with psychological well being on X class students at SMA Negeri 13 Medan. The sample on this study amounted to 142 students. The following instruments were used are Physicological Well Being Scale based on Ryff theory, and Prosocial Behaviour Scale which constructed based on Schroeder and Graziano theory. The results of data analysis using Pearson Product Moment showed r = 0,371 with p = 0.000 (p < 0.05). It means there is a positive and significant between prosocial behaviour with psychological well being on X class students at SMA Negeri 13 Medan, the higher prosocial behaviour are, the higher level of psychological well being on X class students on SMA Negeri 13 Medan.